Influence of pH and electrolyte on the deposition of cerium oxide nanoparticles on supported lipid bilayers. Issue 6 (5th May 2022) - Gu, Wenyu; Liu, Xitong; Yi, Peng
Abstract : The deposition of CeO2 nanoparticles on supported lipid bilayers was governed by DLVO interactions at various pH values and electrolyte concentrations. Abstract : The adhesion of cerium oxide nanoparticles (n-CeO2 ) to cell membranes is likely a crucial step for initiating the toxic effects of n-CeO2 on biological cells. To investigate the propensity of n-CeO2 to adhere to model cell membranes, 1, 2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) supported lipid bilayers (SLBs), the deposition attachment efficiencies of n-CeO2 on SLBs were derived using a quartz crystal microbalance. The impact of solution pH and the valence and concentration of the electrolyte on the attachment efficiency was consistent with the Derjaguin–Landau–Verwey–Overbeek (DLVO) theory. The isoelectric points of DOPC membranes and n-CeO2 are pH 4.2 and 7.2, respectively. At pH 8.0, the attachment efficiency between negatively charged SLBs and n-CeO2 increased with increasing NaCl and CaCl2 concentrations. The critical deposition concentrations of NaCl and CaCl2 are 11 and 0.62 mM, respectively. At pH 2.0 and 4.0, both n-CeO2 and SLBs were positively charged. The attachment efficiency increased as the NaCl and CaCl2 concentrations increased due to charge screening by Cl − anions. At pH 5.5, n-CeO2 and SLBs were oppositely charged in NaCl solutions, hence resulting in favorable attachment. In the presence of CaCl2, however, the adsorption of Ca 2+ cations reversed the charge of SLBs to become positive and thus led to unfavorable deposition. Negligible detachment of n-CeO2 from SLBs was observed upon exposure to low ionic strength solutions or pH changes, indicating irreversible attachment.